p38γ and p38δ Mitogen Activated Protein Kinases (MAPKs), New Stars in the MAPK Galaxy - Escós, Alejandra; Risco, Ana; Alsina-Beauchamp, Dayanira; Cuenda, Ana (Frontiers in Cell and Developmental Biology, 2016)
The protein kinases p38γ and p38δ belong to the p38 mitogen-activated protein kinase (MAPK) family. p38MAPK signalling controls many cellular processes and is one of the most conserved mechanisms in eukaryotes for the cellular response to environmental stress and inflammation. Although p38γ and p38δ are widely expressed, it is likely that they perform specific functions in different tissues. Their involvement in human pathologies such as inflammation-related diseases or cancer is starting to be uncovered. In this article we give a general overview and highlight recent advances made in defining the functions of p38γ and p38δ, focusing in innate immunity and inflammation. We consider the potential of the pharmacological targeting of MAPK pathways to treat autoimmune and inflammatory diseases and cancer